LIQUIDITY RATIO AND PROFITABILITY ANALYSIS TO MEASURE FINANCIAL PERFORMANCE IN PT. ULTRAJAYA MILK INDUSTRY & TRADING COMPANY TBK - Nurwita Nurwita; Rindi Alimah Rodhiah (Yayasan Education and Social Center, 2022)
This study aims to determine the condition of the company's financial performance PT Ulta Jaya Milk Industry & Trading Company Tbk from 2011 to 2020 using a financial ratio measuring instrument. The research method used is a descriptive quantitative method because this research relates to the object of study, namely the company, within a certain period by collecting data and information related to the company and adapting to the research objectives. The data analysis method used is ratio analysis, which describes the relationship between a certain amount and another amount. The analysis used is liquidity and profitability analysis, where the liquidity ratio aims to determine the company's ability to meet its short-term obligations. The results of research using the liquidity ratio from 2011-2020 are seen from the company's current balance in a healthy condition because the average value is 333% above the manufacturing industry standard of 200%. Judging from the Quick Ratio, the company is beneficial because the average value is 237% above the industry standard 150%. While the profitability ratio of the company's ability to generate profits during a certain period. Meanwhile, using the profitability ratio from 2011-2020 seen from the Net Profit Margin, the company is unhealthy because the average value is 13% below the manufacturing industry standard of 20%. Judging from the Return on Assets, the company suffers because the average value is 13% below the manufacturing industry standard of 30%.